2017
DOI: 10.3389/fphar.2017.00763
|View full text |Cite
|
Sign up to set email alerts
|

Intracellular Hyper-Acidification Potentiated by Hydrogen Sulfide Mediates Invasive and Therapy Resistant Cancer Cell Death

Abstract: Slow and continuous release of H2S by GYY4137 has previously been demonstrated to kill cancer cells by increasing glycolysis and impairing anion exchanger and sodium/proton exchanger activity. This action is specific for cancer cells. The resulting lactate overproduction and defective pH homeostasis bring about intracellular acidification-induced cancer cell death. The present study investigated the potency of H2S released by GYY4137 against invasive and radio- as well as chemo-resistant cancers, known to be g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 24 publications
(33 reference statements)
0
24
0
Order By: Relevance
“…Further, Szabo and Papapetropoulos rightly point out that not only H 2 S-poor diseases can be corrected by H 2 S supplementation, since ''there are also several indications where endogenous H 2 S levels are not suppressed, and yet H 2 S donation may be beneficial or warranted.'' Additional evidence, obtained mainly after the list just cited was compiled, supports considering therapeutic application of H 2 S prodrugs in cancer (148), psoriasis (12), multiple viral infections (24,25), colitis (180), autoimmune pathologies (42), systemic sclerosis (2), multiple sclerosis (245), Parkinson's disease (PD) (111), intracerebral hemorrhage (288), Duchenne muscular dystrophy/cardiomyopathy (44), allergic diseases (173), fibrotic disorders (229), osteoarthritis (164), osteoporosis (281), sarcopenia (32), pulmonary hypertension (287), ocular hypertension (225), kidney diseases (15), hearing loss (152), lens opacification (190), testicular dysfunction (262), male subfertility (178), erectile dysfunction (64), and periodontitis (89) as well.…”
Section: H 2 S-poor Diseases and Other H 2 S-treatable Pathologiesmentioning
confidence: 95%
“…Further, Szabo and Papapetropoulos rightly point out that not only H 2 S-poor diseases can be corrected by H 2 S supplementation, since ''there are also several indications where endogenous H 2 S levels are not suppressed, and yet H 2 S donation may be beneficial or warranted.'' Additional evidence, obtained mainly after the list just cited was compiled, supports considering therapeutic application of H 2 S prodrugs in cancer (148), psoriasis (12), multiple viral infections (24,25), colitis (180), autoimmune pathologies (42), systemic sclerosis (2), multiple sclerosis (245), Parkinson's disease (PD) (111), intracerebral hemorrhage (288), Duchenne muscular dystrophy/cardiomyopathy (44), allergic diseases (173), fibrotic disorders (229), osteoarthritis (164), osteoporosis (281), sarcopenia (32), pulmonary hypertension (287), ocular hypertension (225), kidney diseases (15), hearing loss (152), lens opacification (190), testicular dysfunction (262), male subfertility (178), erectile dysfunction (64), and periodontitis (89) as well.…”
Section: H 2 S-poor Diseases and Other H 2 S-treatable Pathologiesmentioning
confidence: 95%
“…Since extracellular acidification also increases the activity of P-gp, in this way inducing MDR in different cancer cells and tissues [ 125 , 128 , 132 ], it becomes logical to associate PPI with PTI, not only to improve the effect of chemotherapy in metastatic BC, but also to overcome MDR. The clinical use of such a combination is considered a fundamental therapeutic measure in any integrated clinical protocol in the treatment of BC [ 4 , 10 , 30 , 31 , 64 , 67 , 68 , 71 , 72 , 73 , 78 , 101 , 122 , 124 , 139 , 140 , 165 , 167 , 174 , 175 , 180 , 188 , 189 , 190 , 195 , 196 , 197 , 202 , 208 , 233 , 307 , 308 , 309 , 310 , 311 ]. The integral pH-related approach to MDR has shown that the therapeutic failure in inducing the acidification of the cytoplasm and/or reverse CPR is the main factor underlying MDR.…”
Section: Other Ph-related Available Therapies In Breast Cancer Trementioning
confidence: 99%
“…Therefore, intracellular acid extruders, such as NHE and MCT, are activated to maintain pH i homeostasis. The overactivation and/or overexpression of the acid extrusion mechanism results in an increased pH i that further promotes proliferation and prevents apoptosis in cancer cells[24,26,28,29]. Furthermore, accompanying extracellular acidification causes restructuring of the extracellular matrix and further promotes malicious metastasis and invasion[26,30,31].…”
Section: Introductionmentioning
confidence: 99%